Metabolic dysfunction-associated steatotic liver disease attenuates the predictive value of the triglyceride–glucose index for carotid plaque: evidence of insulin resistance-independent pathways - Zhang, Fang; Wang, Zheng; Zhang, Han; Zuo, Yu-Qiang (Frontiers in Endocrinology, 2025)
BackgroundInsulin resistance (IR), a key driver of atherosclerosis, is associated with cardiovascular risks such as carotid plaque formation. While the triglyceride–glucose (TyG) index has been established as a reliable surrogate marker of IR, its association with carotid plaque formation in individuals with metabolic dysfunction-associated steatotic liver disease (MASLD) remains to be explored.PurposeThe study investigated whether MASLD modified the association between the TyG index and carotid plaque, hypothesizing that MASLD-specific metabolic pathways attenuate the association between the TyG index and carotid plaque.MethodsA cross-sectional study was conducted in 3414 participants who were stratified into MASLD (n=796) and non-MASLD (n=2618) groups. MASLD was diagnosed by ultrasonography. The TyG index was calculated and its correlation with carotid plaque was evaluated by multivariable logistic regression adjusting for age, sex, body mass index, waist circumference, and metabolic factors. The interaction effects between the TyG index and MASLD status on carotid plaque prediction were evaluated. Receiver operating characteristic analysis compared the discriminatory ability of the TyG index across subgroups.ResultsIn the total cohort, a higher TyG index showed a borderline non-significant association with carotid plaque after comprehensive adjustment for covariates including waist circumference (OR: 1.254, 95% CI: 0.985–1.596; P=0.066). However, stratification by MASLD status revealed a critical effect modification. The TyG index remained a strong, significant predictor in the non-MASLD subgroup (OR: 1.436, 95% CI: 1.066–1.935; P=0.017) but was not associated with plaque in the MASLD subgroup (OR: 0.746, 95% CI: 0.453–1.228; P=0.249). This modification was confirmed by a significant TyG index–MASLD interaction term (OR: 0.532, 95% CI: 0.303–0.937; P=0.029). ROC analysis confirmed the markedly lower discriminatory power of the TyG index in participants with MASLD (AUC: 0.523 vs. 0.629 in non-MASLD, P < 0.001).ConclusionMASLD weakened the association between the TyG index and carotid plaque, suggesting that the underlying pathophysiology may involve mechanisms that alter or decouple the relationship between IR and atherosclerosis.